Pengaruh E-Wom, Lifestyle, Kepercayaan Terhadap Keputusan Pembelian Ticket Online Booking Pada Situs Traveloka.Com Di Ponorogo (Studi Kasus Pembelian Tiket Pesawat Dan Kereta Api) - Vivi Endah Sari (Jurnal Administrasi Bisnis Fisipol Unmul, 2019)
This research is made in order to identify the effect of Electronic Word Of Mouth, Lifestyle, and Trust towards online ticket Buying Decision on Traveloka.com site. Traveloka.com is one of the most famous online ticket buying site in Indonesia. The subject of this research refers to Ponorogo citizens whom have done online ticket buying on Traveloka.com site. The research use  analysis double linear regression, the research took in total 97 samples with probability sampling method. Result of this research shown that Electronic Word Of Mouth, Lifestyle, and Trust has positive and significant influence towards Buying Decision both simultaneously and partially. Meanwhile, the determination coefficient shown 66,1% value for the contribution of Electronic Word Of Mouth, Lifestyle, and Trust and the rest is 33,9% value which is affected by other variable not explained in this research.